Constrained Deterministic Synthesis of Conformal Supershaped Antenna Arrays - Geerarts, Justin M. E.; Theis, Guilherme; Smolders, A. Bart; Caratelli, Diego (IEEE transactions on antennas and propagation, 2023)
Conformal array pattern synthesis represents a challenging problem for current state-of-the-art design techniques. To their detriment, these techniques typically suffer from a significant computational burden. A deterministic method for the synthesis of singly curved conformal antenna arrays based on the superformula and the auxiliary array pattern (AAP) formulation is presented. This method, being semianalytical in nature, is able to evaluate the location and excitation coefficients of each radiating element subject to different design constraints in a deterministic manner while utilizing multiple embedded element patterns. Therefore, this method is more computationally efficient than the state-of-the-art alternatives. The proposed synthesis technique has been validated through full-wave electromagnetic simulations and experimental measurements taken on physical demonstrators relevant to different applications within radar and communication systems. The obtained results show accurate agreement between simulations and measurements, requiring only seconds of computation on conventional hardware.